IMPROVING THE QUALITY OF LEARNING IN MADRASAH IBTIDAIYAH (MI) THROUGH LESSON STUDY (IAIN Metro Partnership Program with MI in Metro City) - Tusriyanto Tusriyanto; Wahyu Setiawan; M. Ihsan Dacholfany; Aprida Kurnia Lestari (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
Lesson Study Program includes the following stages: (1) preparation programs that include: the establishment of organizations and the Division of duties and authorities of the Executive team, assessments in cooperation with related parties; determine the schedule of activities of the Lesson Study; and prepare the instruments and the completeness of the Administration; (2) implementation of programs include: socialization to the teachers, and the school, training to the teachers and the school authorities, the establishment of the operational activities of the Lesson Study and the more operational task Division for the team of researchers, teachers, and principals and implementation of Lesson Study as much as 2 rounds and 6 times the IPS and learning Principles; (3) the evaluation of the activity is focused on the evaluation context, input, process and product. Activity Lesson Study was conducted in two schools in the district Metro Center involving 20 teachers. Implementation of the Lesson Study was: (1) give the results, benefits and impact that is huge for IAIN Metro, the Group of teachers and students in schools in order to improve the quality of learning in MI; (2) able to improve gait in a society with a stakeholder in the synergistic fields especially the school and teachers; (3) a stub for partnership activities of IAIN Metro with MI; and (4) enhance the Simple IAIN Metro Imaging in the community and are expected to push other programs.